Education in Malaysia Developments, Reforms and Prospects - Adams, Donnie (Routledge critical studies in Asian education, 2023)
This book examines Malaysia's ambitious reform agenda and educational landscape, drawing upon the eleven key shifts in the Malaysia Education Blueprint 2013-2025. It provides a comprehensive plan for a rapid and sustainable transformation of the Malaysian education system, and what is needed in shaping the educational reforms in Malaysia, especially post-COVID, through to 2025. The contributors to this volume - scholars, researchers and practitioners who possess a deep and embedded understanding of Malaysian education - focus on the interplay of prevailing and persistent problems, and what is needed in shaping the educational reforms in Malaysia. As a critical assessment of the Malaysian Education Blueprint reform efforts and policies, this edited book will be of particular interest to educators, scholars, and policymakers on the latest trends and challenges in Malaysian education policy